Improving Mathematical Problem Solving of Linear Programs Through Blended Learning Web-Centric Course Model - Raudatul Husna (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2023)
Initial observations given to students showed that the skills to solve math problems were still very low. The low mathematical problem-solving skills of students are due to not being trained to solve math problems. In addition, educators minimally apply varied teaching strategies in every activity of the learning process. The purpose of this study is to examine whether there is an increase in mathematical problem-solving skills in linear program courses for students using blended learning based on web-centric courses. Researchers used quasi-experimental research. The research population is all students of Mathematics Education IAIN Langsa even semester. The research sample was fourth-semester PMA students totaling 40 people. The data collection technique used essay questions. The results of data collection were analyzed by ANOVA. After the data was analyzed using the ANOVA test, this resulted in 0000 <0.05 the level of significance Ho was rejected. From the test results, there is a difference between students whose learning process uses a web-based blended learning model from Centri Course and conventional-based learning. It can be concluded that students who are guided using the Centri Course web-based blended learning model show an increase in completion skills.